Revitalization Management Models – A Comparative Analysis and the Revitalization Operator Model Framework - Lilla KNOP; Agnieszka JANIK; Marek KRANNICH; Adam RYSZKO (Communications of International Proceedings, 2020)
The paper presents a comparative analysis of revitalization management models based on the European experiences and framework of the revitalization operator model in Poland, in particular in the Silesian Voivodeship. Four European countries (i.e. France, Germany, Great Britain and Poland) have been selected for the research where revitalization processes are conducted on a large scale. Strategic approach proposed by the first three countries were benchmarks for the Revitalization Operator Model framework in Poland. The analysis of revitalization management models was conducted in five areas (based on the Business Model Canvas, the New Age of Innovation and Balanced Scorecard conceptions): ownership, organizational, market, resource and financial.
Keywords: Revitalization; Revitalization Management Models; Revitalization Operator